AN EXPERIMENTAL STUDY ON THE ANTI-EHRLICH ASCITES CARCINOMA EFFECT OF PURIFIED TOAD VENOM EXTRACT - Wang, Ying (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of this paper was to study the anti-Ehrlich ascites carcinoma effect of purified toad venom extract and its mechanism. Mouse model of Ehrlich ascites carcinoma was established with cisplatin as the control to observe the inhibitory effect of purified toad venom extract on malignant peritoneal effusion in mice. The results showed that compared with the control group, ascites volume, number of tumour cells and tumour cell viability decreased and ascites inhibition rate reached over 50% in each treatment group, and with the increase of the dose, incidence of ascites showed a downward trend. The number of tumour cells in ascites and tumour cell viability in the purified toad venom high-dose group were lower than those of the cisplatin group. Compared with the model group, survival time was prolonged in varying degrees in the purified toad venom groups and cisplatin group. The study concluded that purified extract of toad venom has an anti-Ehrlich ascites carcinoma effect.